Detection of light transmittance of liquids using an electronic circuit. - Sanaa Alnajjar; Jameel Sulaiman (College of Education for Pure Sciences, 2009)
Abstract Transmissivity detections of the light for liquids by using electronic circuit which consists in the main part, detector type (CdS: cadmium Sulphide). The principle operation of this detector depends on the quantity of incident light on it, where its resistance decreases while the incident light increases, and its resistance increases when there is no light [7]. The test operation obtained through the use of electronic circuit. It is found that the resistance value of the detector is (11441.6) Ohm, when there is no light (Dark), and for the sample of mercury in its path detector (11415.5) Ohm, while the resistance detector for the transparency liquid such as glycerin and kerosene is denoted to (11210.7) Ohms. So, this is a clear sign to prove the transmissivity of light in liquids by using electronic circuit.